THE IMPACT OF BUSINESS ETHICS ON ENHANCING SERVICE QUALITY BY APPLYING E-BUSINESS TECHNOLOGIES IN HEALTH INSTITUTIONS - Al-Mayali, Hakim Ihsouni; Al-Ardawi, Yahya Habib Shaneen (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to show the effect of business ethics as an independent variable by its dimensions (individual ethics, leadership ethics, activities ethics, organizational structures ethics) on the quality of service as an approved variable through its dimensions (reliability, time, response, assertion) through the application of electronic business technologies as an intermediate variable with its dimensions (Electronic infrastructure, application of hospital electronic business systems, health information systems),Given the importance of the topic in the health sector and its impact on the lives of most people, therefore the research was conducted in (3) government hospitals in the Najaf Al-Ashraf , as the opinions of a sample of (200) individuals working in health institutions were explored, and this was done through the questionnaire as a main tool in Obtaining data and information, as well as personal interviews, as well as Arab and foreign sources and references.